The exploration of empowerment: participation of urban agriculture communities with presence of social capital - Nazur, Nur Shuhamin; Ahmad, Nobaya; Rosnon, Mohd Roslan; Rosidi, Mohd Harifadilah; Nazuri, Siti Nur Shuhada; Mohd Salim, Sara Shakilla; Sazali, Razif; Ahmad, Mohamad Firdaus; Ahmad Suhaimi, Siti Shazwani (Human Resource Management Academic Research Society, 2022)
In Malaysia, Urban Agriculture program’s initiative has brought local communities together to grow their own food in designated areas and at the same time to empower the community (Bernama, 2020). According to Strzelecka et al (2017) participation is important in strengthening community empowerment. However, lack of participation among UA community resulted investment and initiative done by government to waste. This study aims to identify dimension of participation (planning, implementation and evaluation) level of Urban Agriculture (UA) program’s respondents towards economic and social empowerment independently, where their effect is design to be moderated by social capital consisting of bonding, bridging and linking. This study recorded majority of the respondents were male, aged between 41-60 years old, married and has obtained secondary school/vocational. Majority of them have family members between 5 to 12. Addition to that, relationship between participation, social capital towards empowerment among respondents were found to be insignificant. Hence, resulting social capital (bonding, bridging and linking) do not have moderator function on participation to empowerment. Several recommendations for future studies were discussed. First, other new variable should be examined and future research will consider using qualitative methods to conduct in-depth discussions in order to identify any additional variables with the potential to influence empowerment of UA program’s respondents. Secondly, future studies should consider in looking factors effecting of weak networking social capital, and the aspects of strengthening participation of UA program’s respondents. Thirdly, other possible factors that possibly influence the empowerment of UA program’s respondents should be investigate. It is anticipated that findings can be used as a basis for the future research related to UA program in Malaysia.